2020
DOI: 10.5811/westjem.2020.6.46300
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder in Family-witnessed Resuscitation of Emergency Department Patients

Abstract: Introduction Family presence during emergency resuscitations is increasingly common, but the question remains whether the practice results in psychological harm to the witness. We examine whether family members who witness resuscitations have increased post-traumatic stress disorder (PTSD) symptoms at one month following the event. Methods We identified family members of critically ill patients via our emergency department (ED) electronic health record. Patients were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Over 90% of nurses thought that the experience of witnessing the management of an acutely deteriorating patient may cause emotional trauma and stress for the patient's family. It is true that families experiencing the acute deterioration of a loved one may become emotional and require additional support ( 14 ) and are even at risk of developing Post Traumatic Stress Disorder ( 31 ). These situations may place health care practitioners in a difficult position and while consideration for the support of families during this process is vital, there is a lack of objective data supporting these concerns and the risk should not hinder the implementation of good practice( 26 )( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 90% of nurses thought that the experience of witnessing the management of an acutely deteriorating patient may cause emotional trauma and stress for the patient's family. It is true that families experiencing the acute deterioration of a loved one may become emotional and require additional support ( 14 ) and are even at risk of developing Post Traumatic Stress Disorder ( 31 ). These situations may place health care practitioners in a difficult position and while consideration for the support of families during this process is vital, there is a lack of objective data supporting these concerns and the risk should not hinder the implementation of good practice( 26 )( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…These situations may place health care practitioners in a difficult position and while consideration for the support of families during this process is vital, there is a lack of objective data supporting these concerns and the risk should not hinder the implementation of good practice( 26 )( 32 ). Fundamentally, studies show that family members prefer to be given a choice and strongly believe that it is their right to be present ( 26 , 31 ). Family centred care is not only about physical presence but also about self-determination and allowing the family and patient the right to choose ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the largest randomised trial conducted so far family members witnessing the resuscitation efforts had significantly less post-traumatic stress disorder (PTSD)-related symptoms8 9 However, a prospective comparison group study reported no impact of witnessing CPR on bereavement-related depression and PTSD symptoms10 while observational studies showed no meaningful effects of family presence11 or even an increase in PTSD-related symptoms 12 13…”
Section: Introductionmentioning
confidence: 99%
“…It is controversially discussed whether the risk for post-traumatic stress disorder in relatives is increased or decreased, when they are present during emergency team-led cardiopulmonary resuscitation (CPR) [12][13][14][15][16]. Mathiesen and colleagues interviewed 20 bystanders, who performed CPR, on how they processed this event and found that some struggled in life (feelings of guilt, reduced work capacity, weight loss, flashbacks and nightmares) even years after the event [17].…”
Section: Introductionmentioning
confidence: 99%